Project modelling in construction seeing is believing - Fisher, Norman, 1946- (Thomas Telford, 1997)
This book has been written to look at the current state of development of object oriented modelling and at the competitive advantages and pitfalls it will bring in the future.
Keywords: Construction industry -- Data processing.; Simulation methods.; elektronické knihy; electronic books